The Tool for Quality Estimation of Short Voice Segments - Anskaitis, A.; Kajackas, A. (Elektronika ir Elektrotechnika, 2010)
It is recognized that objective and reliable voice quality measure is PESQ algorithm. Systemic analysis of impact of packet loss on voice quality using PESQ raises some problems because each and every packet has distinct impact on speech quality and long signal as required in ITU specification [2] contains a lot of positions for possible packet losses. When there are a few lost packets in single measurement, the quality measured become a random number. The generalized conclusions about impact of packet loss on voice quality may be educed after many measurements performed using different combinations of lost packets. In this paper proposed tool for quality measurement of short segments using composite measurement signal with conventional PESQ algorithm. It is shown that the proposed tool is compatible with existing PESQ algorithm. The measurement results obtained using composite signals are compatible with those generated by standard PESQ. The proposed tool with composite measurement signal reduces the amount of experiments because the number of voice frames is smaller in short sentences.